2019
DOI: 10.1080/10106049.2019.1573928
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between MODIS EVI and LAI across time and space

Abstract: The Leaf Area Index (LAI) is used as input in hydrological and biochemical models for the estimation of water-cycle characteristics, agricultural primary production and other processes. Vegetation Indices (VIs) are used to monitor vegetation state and health. Considering that easily computed VIs can be used for the estimation of LAI, this study applied a regression analysis between MODIS Enhanced Vegetation Index (EVI) and LAI data in five sites around the world. A linear model was found to provide a good desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In agriculture, LAI is essential for, among others, monitoring the variability in crops and rangelands productivity, crop stress and health, biomass, phenology, and yield estimation (Mulla 2013;Cho, Ramoelo, and Dziba 2017;Novelli et al 2019). Unfortunately, traditional direct LAI (in-situ) measurement methods are spatially and temporally limited, expensive, time-consuming, labour-intensive, and destructive (Alexandridis et al 2013). Therefore, remotely sensed effective LAI (hereafter, LAI) provides a promising alternative for operational agricultural monitoring to support the implementation of global and regional food security mandates such as the United Nations Sustainable Development Goals (UN-SDGs) and Agenda 2063.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agriculture, LAI is essential for, among others, monitoring the variability in crops and rangelands productivity, crop stress and health, biomass, phenology, and yield estimation (Mulla 2013;Cho, Ramoelo, and Dziba 2017;Novelli et al 2019). Unfortunately, traditional direct LAI (in-situ) measurement methods are spatially and temporally limited, expensive, time-consuming, labour-intensive, and destructive (Alexandridis et al 2013). Therefore, remotely sensed effective LAI (hereafter, LAI) provides a promising alternative for operational agricultural monitoring to support the implementation of global and regional food security mandates such as the United Nations Sustainable Development Goals (UN-SDGs) and Agenda 2063.…”
Section: Introductionmentioning
confidence: 99%
“…However, the validation of SNAP-derived LAI from Sentinel-2 data, as well as its consistency with existing LAI products, were explored by few studies (Bochenek et al 2017;Campos-Taberner et al 2018). This is indispensable since accurate and reliable agricultural monitoring strongly hinges on the consistency and inter-comparability of biophysical parameters such as LAI (Alexandridis, Ovakoglou, and Clevers 2019). Furthermore, uncertainties related to the effect of the spatial resolution and processing level of the data on derived biophysical parameters such as LAI need further assessment, especially in Africa, where such studies are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The MODIS LAI-EVI relationship was examined through regression analysis, taking into account both the characteristics of seasonality (Day of Year, DOY) and the vegetation type (T. K. Alexandridis, Ovakoglou, & Clevers, 2019). The regression analysis was applied using a linear fit (y = a + b * x) for each available pair of a MODIS LAI and EVI image of the same period and for each study area, while the data were grouped per vegetation type.…”
Section: Modis Lai-evi Regression Equations For the Downscaling Modelmentioning
confidence: 99%
“…After the application of the regression analysis, the equations that connected MODIS LAI with MODIS EVI per date and vegetation type were generated for each test site. An example of the regression analysis results for the study area of Umbeluzi on DOY 193-2013 can be found in Table 6, while a detailed presentation of all results is available at T. K. Alexandridis et al (2019). In all vegetation types of Umbeluzi, the probability value (p) was <0.0001.…”
Section: Modis Lai-evi Regression Analysismentioning
confidence: 99%
“…A number of studies on various vegetation types have led to the general conclusion that spectral vegetation indices may be considerably sensitive to LAI/FPAR changes [55][56][57][58]. The normalized difference vegetation index (NDVI) is one of the most extensively used vegetation indices related to LAI/FPAR [57].…”
Section: Estimation Of Ahi Lai/fpar Using Annmentioning
confidence: 99%